Promoting Critical Thinking Skills through Contextual Teaching and Learning - Rahmat Ramadansur; Al Khudri Sembiring; Ramanda Rizky; Nelvariza Nelvariza (Lectura : Jurnal Pendidikan, 2023)
Critical thinking skills are one of many skills that should be acquired by students in the 2013 curriculum, and it allows students to be able to think critically in learning. However, the delicacy of the learning methods or models used in biology learning was found since the teacher mostly used lecture methods and assignments. In order to overcome these problems and achieve educational goals, the role of teachers who acquire appropriate learning methods and models according to the subject they teach is very important, and the Contextual Teaching and Learning is one of many appropriate methods that can be used. Therefore, this study aims at determining the impact of the Contextual Teaching and Learning regarding to students’ critical thinking skills at Sekolah Menengah Atas Negeri (SMAN) 16 Pekanbaru. Moreover, a quantitative research was used as the method of the research. According to the data analysis, it was found that the average score of the critical thinking test in the control class was 2.33 and it was classified into moderate. In other hand, and the average score in the experimental class was 2.53 and it was categorized as high. As a result, the Contextual Teaching and Learning was able to give siginificant influence related to students critical Thinking Skills. This was occured since the method is focused on describing the competencies that teachers should achieve first at the beginning of learning.